Charismatische Spiritualität und Seelsorge : der Volksmissionskreis Sachsen bis 1990 - Schmidt, Markus 1986- (Kirche - Konfession - Religion, 2017)
Markus Schmidt's study provides an important contribution to the study of the church, piety and biographical history of the Saxon Landeskirche in the 20th century. The Volksmissions Kreis (People's Mission District) was in the GDR (German Democratic Republic) at the head of the charismatic movement of Saxony and was decisive in its distribution within Evengelical-Lutheran Country church. The concept of spirituality and the pastoral care of the district still characterize the Saxon Landeskirche. Markus Schmidt examines the Volksmissionskreis from its roots in the Confessing Church up to the time of the Peaceful Revolution. He analyzes the pastoral care concept of the district and discusses his pastoral care practice critically